THE POLICY OF CRIMINALIZATION AND PUNISHMENT IN THE EFFECTIVE IRAQI TRAFFIC LAW: A COMPARATIVE ANALYTICAL STUDY - Huda Abbas Mohammed Ridha Al-Shammaa; Hayder Abdul jaleel Mahdi; Mohammed Hassan Jassim (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The legislator should develop a policy of criminalization and punishment that would set a standard for criminalization, whether based on risk or harm, under explicit provisions so that it is not subject to interpretation by thejudiciary.For example, suppose criminal images are identified. In that case, the punishment should be appropriate for each crime with its physical and moral entity on the one hand and on the other to ensure that criminal conduct is reduced. When we say an appropriate punishment, it should be tolerated, such as dropping it or prioritizing the negative punishment of freedom.